Discourse on Goli otok from a female perspective (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper aims to reconstruct the emergence of female discourse which is focused on camps for Informbiro adherents. These female testimonies were excluded from mainstream history and literature because, on the one hand, the issue of Goli otok Camp (Barren Island Camp) was a taboo issue, and, on the other hand, because of the dominance of the male narratives. The subordination and, moreover, the nonexistence of mainstream female memoirs persisted until Danilo Kiš got interested in women’s prison camp experience. Documentary series Goli život (Barren life) was filmed on his initiative in 1989. Danilo Kiš also inspired Ženi Lebl to write down her own history. That was the first camp testimony published by a woman (Ljubičica bela. Vic dug dve i po godine 1990/ The White Violet. Two and a half year long joke). A recent study showed that another camp prisoner, Milka Žicina, was writing about her camp experience during the 1970s, but was hiding the manuscript in fear of repression. Her texts were published posthumously in the journals Dnevnik (1993) and Letopis Matice srpske (1998).
Keywords: Goli otok camp; female discourse; Danilo Kiš; Ženi Lebl; Milka Žicina